Internalisasi Kearifan Lokal Dalam Tradisi Dewa Mesraman Di Desa Paksabali Kabupaten Klungkung (Perspektif Nilai-Nilai Pendidikan) - Brahmani Putri, Ida Ayu Nindia; Sudarsana, I Ketut (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2023)
Dewa Masraman is a tradition of the people of Banjar Timbrah, Pasekbali Village, Klungkung Regency which is held every six months, as a form of game and a symbol of the gods having fun. Many refer to the ceremony as the Dewa Mepalu ceremony, the god's battle ceremony. The real clash was Ida Bhatara's sulking (gathering) action because they had not seen each other for a long time. In the Masraman procession, there are 7 jolly gods who participate. The Dewa Mesraman tradition is still well guarded by the entire community of Paksebali Village as a form of internalizing local wisdom about the meaning of the tradition. In addition, the Dewa Mesraman Tradition is also full of meaning, even if examined contains various studies on Hindu Religious Education which are in line with the basic tri-framework of Hinduism as well as educational values ​​that are able to form a stable personality for all Paksebali Village people in simultaneously implementing the Dewa Masraman Tradition as a form of religious activity. which is highly respected by the people in Paksebali Village.